Предмет: Алгебра,
автор: vzcybrjdf
решите уравнение: (0,7х-2,1)-(0,5-2х)=0,9(3х-1)+0,1
Ответы
Автор ответа:
0
(0,7x - 2,1 )- 0,5+2х =0,9 (3х-1) + 0,1
-0,35х+ 1,05 + 2х =2,7х -0,9 +0,1
-0,35х+2х -2,7х = -0,9+0,1+1,05
-1,05х =0,25
х= -1,05 : 0,25
х= -4,2
-0,35х+ 1,05 + 2х =2,7х -0,9 +0,1
-0,35х+2х -2,7х = -0,9+0,1+1,05
-1,05х =0,25
х= -1,05 : 0,25
х= -4,2
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: География,
автор: ЕвгенияМор
Предмет: География,
автор: pkartasova137
Предмет: Физика,
автор: wind8